2014
DOI: 10.7314/apjcp.2014.15.11.4723
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Breast Cancer Warning Signs and Screening Methods among Female Residents of Pokhara Valley, Nepal

Abstract: Background: Breast cancer is the second most common cancer in the world and by far the most frequent cancer among women. Objective: The present study was undertaken to assess the awareness of breast cancer warning signs and screening methods among the women of Pokhara valley, Nepal. Materials and Methods: A cross-sectional questionnaire survey was carried out in a community setting with the female population. The questionnaire was administered in face-to-face interviews by trained research assistants. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 10 publications
8
56
1
Order By: Relevance
“…The findings indicated that the level of awareness of BC is sub-optimal among the women participants of Delhi. Our overall results are consistent with studies done in other parts of the India (Somdatta and Baridalyne, 2008;Gupta, 2009;Khokhar, 2009;Yadav and Jaroli, 2010;Shalini et al, 2011;Grosse et al, 2013;Parameshwari et al, 2013;Sathian et al, 2014;Sreedevi et al, 2014) and world (Okobia et al, 2006;Elsie et al, 2010;Forbes et al, 2011;Samganje and Mafuvadze, 2012;Radi, 2013;Karadag et al, 2014;Kratzke et al, 2014;Asif et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings indicated that the level of awareness of BC is sub-optimal among the women participants of Delhi. Our overall results are consistent with studies done in other parts of the India (Somdatta and Baridalyne, 2008;Gupta, 2009;Khokhar, 2009;Yadav and Jaroli, 2010;Shalini et al, 2011;Grosse et al, 2013;Parameshwari et al, 2013;Sathian et al, 2014;Sreedevi et al, 2014) and world (Okobia et al, 2006;Elsie et al, 2010;Forbes et al, 2011;Samganje and Mafuvadze, 2012;Radi, 2013;Karadag et al, 2014;Kratzke et al, 2014;Asif et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Recent study done on awareness of BC warning signs and screening methods among female residents of Pokhara Valley at Nepal by Sathian et al (2014) also supported finding by adding that high SES women are exposed to health-related issues through mass media, internet and a better socioeconomic status enables support of screening services. Similar associations with SES were observed by Kanaga et al in Malaysia (Kanaga et al, 2011) and Amin et al in Saudi Arabia when enquiring about BC gene testing awareness (Amin et al, 2012).…”
Section: Discussionmentioning
confidence: 75%
“…Some domains of the B-CAS were consistent with those identified in previous research including, knowledge of risk factors, signs and symptoms and barrier to breast screening (Al-Dubai et al, 2011;Norsa'adah et al, 2012;Sathian et al, 2014;Tazhibi and Feizi, 2014;Yousuf et al, 2012). In addition to these commonly used domains, we identified domains not included in a large majority of existing instruments.…”
Section: Discussionsupporting
confidence: 80%
“…In Asian countries, breast cancer is the most diagnosed female cancer and increasing incidence has been observed in several Asian countries (Long et al, 2010;Youlden et al, 2014). This has led to several studies investigating the actual problem by way of studying breast cancer awareness (Khokhar, 2009;Al-Dubai et al, 2011;Kanaga et al, 2011;Gurdal et al, 2012;Wu et al, 2012;Yoo et al, 2012;Donnelly et al, 2013;Norlaili et al, 2013;Radi, 2013;Liu et al, 2014;Sathian et al, 2014;Miyawaki, Shibata et al, 2014;Tazhibi and Feizi, 2014). Most studies have found that the awareness of breast cancer in developing countries was weak compared with developed countries (Jones et al, 2010;Kwok et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation